Bodily Complexity: Integrated Multicellular Organizations for Contraction-Based Motility - Arnellos, Argyris; Keijzer, Fred (Frontiers in Physiology, 2019)
Compared to other forms of multicellularity, the animal case is unique. Animals—barring some exceptions—consist of collections of cells that are connected and integrated to such an extent that these collectives act as unitary, large free-moving entities capable of sensing macroscopic properties and events. This animal configuration is so well-known that it is often taken as a natural one that ‘must’ have evolved, given environmental conditions that make large free-moving units ‘obviously’ adaptive. Here we question the seemingly evolutionary inevitableness of animals and introduce a thesis of bodily complexity: The multicellular organization characteristic for typical animals requires the integration of a multitude of intrinsic bodily features between its sensorimotor, physiological, and developmental aspects, and the related contraction-based tissue- and cellular-level events and processes. The evolutionary road towards this bodily complexity involves, we argue, various intermediate organizational steps that accompany and support the wider transition from cilia-based to contraction/muscle-based motility, and which remain insufficiently acknowledged. Here, we stress the crucial and specific role played by muscle-based and myoepithelial tissue contraction—acting as a physical platform for organizing both the multicellular transmission of mechanical forces and multicellular signaling—as key foundation of animal motility, sensing and maintenance, and development. We illustrate and discuss these bodily features in the context of the four basal animal phyla—Porifera, Ctenophores, Placozoans, and Cnidarians—that split off before the bilaterians, a supergroup that incorporates all complex animals.